J. P.'s call to R.S.S. - Narayan, Jayaprakash, 1902-1979 (Jagarana Prakashana, 1979)
Speech, originally delivered in Hindi at the Rashtriya Swayam Sevak Sangh Training Camp in Patna on November 3, l977.